Evaluasi Waktu Kerja Efektif Alat Gali Muat dalam Rangka Meningkatkan Pendapatan dari Harga Penjualan Batubara pada PT. Britmindo site Bukuan, Kecamatan Palaran, Kota Samarinda, Kalimantan Timur. - Wisma Hidayat; Rijal Abdullah; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2018)
The things that should be success parameter of mining company is the amount of its production. Loading and hauling equipments performance will determine production planning. Unproductive working hours directly also be an affect from unappropiate work system. As the draft of this research, the author examine the data of its equipments cycle time so that it can be obtained the details working hours of equipments such as effective working hours, and working hours obstacles. The methodology of this research used quantitative analysis approachment which the biggest point should be done to reach the goals of this research is to examine the data and make a detail of working hours such as the number of annual equipments and then evaluated it, thus it would be obtained the production. The results showed the average of equipments was working about 3.55 hours/day with production getting (25,417.997 ton). Then the autors do an evaluation, if working hours is increased to 5 hours/day, then it also will increase more than (35,819.3467 ton) and additional revenue from (Rp. 12,708,998,500) be (Rp. 17,909,673,800).